Immunogenicity and safety of Gardasil among mid-adult aged men (27–45 years)—The MAM Study. Issue 42 (13th October 2015) - Giuliano, Anna R.; Isaacs-Soriano, Kimberly; Torres, B. Nelson; Abrahamsen, Martha; Ingles, Donna J.; Sirak, Bradley A.; Quiterio, Manuel; Lazcano-Ponce, Eduardo
Highlights: The quadrivalent HPV vaccine was administered to mid-adult men ages 27–45 years. 100% of men seroconverted to each of the four HPV vaccine components. Immune response to vaccine in men ages 27–45 was comparable to that in younger men. Antibody response did not differ by age group or sexual orientation. No serious adverse events attributable to vaccination were observed. Abstract: Background: The quadrivalent (types 6/11/16/18) human papillomavirus (HPV) vaccine, Gardasil, has demonstrated efficacy against persistent HPV infection and associated anogenital disease in males. The goal of this Phase II trial was to establish the immunogenicity and safety of Gardasil among mid-adult men ages 27–45 years. Methods: One hundred and fifty men from Tampa, FL, US, and Cuernavaca, Mexico who met eligibility criteria (male, 27–45 years old, completed four years of follow-up in the HPV Infection in Men (HIM) natural history study) were enrolled. Subjects completed four visits over seven months, with Gardasil administered at Day 1 and Months 2 and 6. Sera were collected at Day 1 (pre-vaccination) and Month 7 (one month post-dose three). Anti-HPV6, 11, 16, and 18 IgG levels were determined by competitive Luminex immunoassay. Findings: 100% of men seroconverted to each of the four HPV vaccine components, and the vaccine was generally well-tolerated. Antibody responses to vaccine did not differ by age group or sexual orientation, regardless of HPV type, and were significantly higher at Month 7 among men who entered the trial seropositive for HPV 6 or 11. Interpretation: The immune response to HPV vaccination in men ages 27–45 was comparable to that observed in younger men, in whom clinical efficacy was demonstrated. Further trials to assess the efficacy of HPV vaccines to prevent persistent HPV infections in mid-adult men are needed. Funding: Merck & Co. Inc. was the main sponsor of this trial (IISP39256) and provided the study product.